Enteropeptidase inhibitor SCO-792 effectively prevents kidney function decline and fibrosis in a rat model of chronic kidney disease. Issue 4 (22nd December 2020) - Katayama, Yuko; Sugama, Jun; Suzuki, Tomohisa; Ishimura, Yoshimasa; Kobayashi, Akihiro; Moritoh, Yusuke; Watanabe, Masanori
Abstract: Background: Inhibiting enteropeptidase, a gut serine protease regulating protein digestion, suppresses food intake and ameliorates obesity and diabetes in mice. However, the effects of enteropeptidase inhibition on kidney parameters are largely unknown. Here, we evaluated the chronic effects of an enteropeptidase inhibitor, SCO-792, on kidney function, albuminuria and kidney pathology in spontaneously hypercholesterolaemic (SHC) rats, a rat chronic kidney disease (CKD) model. Methods: SCO-792, an orally available enteropeptidase inhibitor, was administered [0.03% and 0.06% (w/w) in the diet] to 20-week-old SHC rats showing albuminuria and progressive decline in glomerular filtration rate (GFR) for five weeks. The effects of SCO-792 and the contribution of amino acids to these effects were evaluated. Results: SCO-792 increased the faecal protein content, indicating that SCO-792 inhibited enteropeptidase in SHC rats. Chronic treatment with SCO-792 prevented GFR decline and suppressed albuminuria. Moreover, SCO-792 improved glomerulosclerosis and kidney fibrosis. Pair feeding with SCO-792 (0.06%) was less effective in preventing GFR decline, albuminuria and renal histological damage than SCO-792 treatment, indicating the enteropeptidase-inhibition-dependent therapeutic effects of SCO-792. SCO-792 did not affect the renal plasma flow, suggesting that its effect on GFR was mediated by an improvement in filtration fraction. Moreover, SCO-792 increased hydrogen sulphide production capacity, which has a role in tissue protection. Finally, methionine and cysteine supplementation to the diet abrogated SCO-792-induced therapeutic effects on albuminuria. Conclusions: SCO-792-mediated inhibition of enteropeptidase potently prevented GFR decline, albuminuria and kidney fibrosis; hence, it may have therapeutic potential against CKD.